IL‐17F co‐ ;expression improves cell growth characteristics and enhances recombinant protein production during CHO cell line engineering1. Issue 4 (23rd November 2012) - Contie, Mathias; Leger, Olivier; Fouque, Nicolas; Poitevin, Yves; Kosco‐Vilbois, Marie; Mermod, Nicolas; Elson, Greg
Abstract The generation of a high productivity cell line is a critical step in the production of a therapeutic protein. Many innovative engineering strategies have been devised in order to maximize the expression rate of production cells for increased process efficiency. Less effort has focused on improvements to the cell line generation process, which is typically long and laborious when using mammalian cells. Based on unexpected findings when generating stable CHO cell lines expressing human IL‐17F, we studied the benefit of expressing this protein during the establishment of production cell lines. We demonstrate that IL‐17F expression enhances the rate of selection and overall number of selected cell lines as well as their transgene expression levels. We also show that this benefit is observed with different parental CHO cell lines and selection systems. Furthermore, IL‐17F expression improves the efficiency of cell line subcloning processes. IL‐17F can therefore be exploited in a standard manufacturing process to obtain higher productivity clones in a reduced time frame. Biotechnol. Bioeng. 2013; 110: 1153–1163. © 2012 Wiley Periodicals, Inc.